2017
DOI: 10.1111/1467-9477.12094
|View full text |Cite|
|
Sign up to set email alerts
|

How Election Polls Shape Voting Behaviour

Abstract: This article investigates how election information such as opinion polls can influence voting intention. The bandwagon effect claims that voters ‘float along’: a party experiencing increased support receives more support, and vice versa. Through a large national survey experiment, evidence is found of a bandwagon effect among Danish voters. When voters are exposed to a news story describing either an upwards or downwards movement for either a small or large party, they tend to move their voting intentions in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
1
16
0
2
Order By: Relevance
“…Moreover, the finding that it appears to be positive, and not negative poll coverage that affect subsequent coverage is also in line with a number of recent studies of exposure to poll coverage on voters conducted in multi-party systems. For example, both Dahlgaard et al (2017) and Van der Meer et al (2016) have found that framing of positive poll stories increase vote intention for parties, while there were no corresponding effect for negative stories. Both these two explanations should, however, be viewed as provisional, and something that would need to be evaluated on a new empirical material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the finding that it appears to be positive, and not negative poll coverage that affect subsequent coverage is also in line with a number of recent studies of exposure to poll coverage on voters conducted in multi-party systems. For example, both Dahlgaard et al (2017) and Van der Meer et al (2016) have found that framing of positive poll stories increase vote intention for parties, while there were no corresponding effect for negative stories. Both these two explanations should, however, be viewed as provisional, and something that would need to be evaluated on a new empirical material.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that evidence of the bandwagon effect has been mixed (Moy & Rinke, 2012). However, considering the extensive and persistent interest in how poll results might influence opinion formation (Rothschild & Malhotra, 2014;Toff, 2018) and political behavior among voters (Dahlgaard et al, 2017;Stolwijk et al, 2016;Van der Meer et al, 2016), it is somewhat puzzling that so few studies have considered how the media's publication of poll results might influence subsequent political coverage (Toff, 2016).…”
Section: The Game Frame Within Political Journalismmentioning
confidence: 99%
See 1 more Smart Citation
“…Hodgson y Maloney (2013) o Gelman y King (1994) han analizado cómo los votantes aprenden del pasado: los efectos podrían ser menos influyentes en su comportamiento electoral si anteriormente las encuestas han fallado considerablemente acerca del resultado final o si los votantes perciben intenciones partidistas o ideológicas para alterar su comportamiento electoral. Además, Van der Meer et al (2016) o Dahlgaard et al (2017) demuestran que los estudios acerca del bandwagon no presentan efectos a largo plazo en el comportamiento electoral de los votantes o en el sistema de partidos.…”
Section: Los Efectos Políticos De Los Sondeos Preelectoralesunclassified
“…This argument, considered elsewhere in proportional representation contexts (Dahlgaard et al, 2017; Irwin and Van Holsteyn, 2000; Stolwijk et al, 2017) is worth comparing with the dominance of the static approach, which is arguably more applicable in ‘winner-takes-all’ contexts (Irwin and Van Holsteyn, 2000: 9). It is apparent that the context in which these effects are studied is central to determining which type of comparison is salient.…”
Section: A Typology Of Bandwagon Effectsmentioning
confidence: 99%